GE_GERICHTE P/14328/2022 vom 8. Mai 2023 - GE Cour de justice (2023)
EXPULSION(DROIT PÉNAL);LOI FÉDÉRALE SUR LES ÉTRANGERS ET L'INTÉGRATION;DISPOSITIONS PÉNALES DE LA LEI | LEI.119.al1; CPP.389.al1; CP.66.letabis